Microplastic ingestion by Atlantic chub mackerel (Scomber colias) in the Canary Islands coast. (February 2019) - Herrera, A.; Ŝtindlová, A.; Martínez, I.; Rapp, J.; Romero-Kutzner, V.; Samper, M.D.; Montoto, T.; Aguiar-González, B.; Packard, T.; Gómez, M.
Abstract: In recent years, due to the increasing concerns about their negative impact on wildlife and possible toxicity to living organisms (including humans), microplastics have become the subject of intense investigations. In the ocean, microplastics can be easily ingested by numerous marine organisms because of their small size (<5 mm). The Northwest African upwelling system is an important fishery area, and the present study is the first one in the region to reveal the presence of microplastic particles in the digestive tract of Atlantic chub mackerel ( Scomber colias ). From the 120 examined fish gastrointestinal tracts, 78.3% contained some type of microplastics, 74.2% contained fibres, 17.5% plastic fragments, and 16.7% paint. More studies are needed on fish, but S. colias is a candidate for being a good indicator of microplastic contamination in the region. Highlights: Ingestion of microplastics by fish around the Canary Islands was documented for the first time. Microplastics were found in the digestive tract of 78.4% of the sampled fish. Fibres comprised 74.2% of the microplastics found. We hypothesize that high fibres incidence may be related to untreated wastewater discharges. Scomber colias could be a good indicator of microplastic contamination in the region.